Strategi Public Relations Bali Hai Cruise Sebagai Penyedia Atraksi Wisata Bahari Di Desa Lembongan, Kecamatan Nusa Penida, Kabupaten Klungkung - Septiani, Made Sera; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA, 2019)
Bali Hai Cruise is one of the companies engaged in marine tourism at Lembongan village, Klungkung regency. The cruise has been established for 28 years and until now still maintained its existence as one providers of the marine tourism providers in Bali. They offer exclusive day trips at Lembongan just in one day. This research aims to provide an overview of the marine tourism attractions and find out public relations strategy of Bali Hai Cruise. This research uses qualitative data. Data is collected by observation, interview and literature study. There are several key concepst of this research, such as: strategy, public relations, public relations strategy, and marine tourism. The result of the research shows that Bali Hai Cruise have a public relations strategy based on internal company relationship by maintaining the quality of human resources and still give attention on the right employee, although the company has not been consistent in financial management. While on external company relations, Bali Hai Cruise is focusing on maintaining the image and brand of the company, even though the company still gets protests from the public because of coastal private beach. Keywords: marine tourism, public relations, internal relations, external relations